Integrative counseling - Kottler, Jeffrey A. (Boston, MA : Allyn & Bacon Professional, 2002)
In this video, Dr. Kottler clearly practices what he preaches, demonstrating a high degree of interpersonal authenticity as well as pragmatic flexibility
Moderator: Jon Carlson, Diane Kjos
Keywords: Psychotherapy; Counseling